x = 2
6-3x = 5x-10x+10 6-3x = -5x+10 -3x+5x = 10-6 2x = 4 x = 2
so 3x + 2 = x + 12 ie 2x = 10 x =5
X=2
3x - 2 = 2x + 4 3x - 2x = 4 + 2 x = 6
x=2
x = 2
4x + 10 + 3x = 40 - 3x 4x + 10 + 3x + 3x = 40 20x = 40 x = 2
y=x-2
3x+4=10 To solve: 3x+4=10 3x=6 x=2
x = -4 and y = 2
6-3x = 5x-10x+10 6-3x = -5x+10 -3x+5x = 10-6 2x = 4 x = 2
x = -5 x = 2
x = 7 and 2/3
3x + 2 = Y
The equation can be solved by isolating the variables from the numbers. The answer would be 4x = 8, which equals 2.
8x + 6 = 3x - 4 8x = 3x - 4 - 6 8x = 3x - 10 8x - 3x = -10 5x = -10 5x/5 = -10 x = -10/5 x = -2